2021
DOI: 10.7759/cureus.15154
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in Transcatheter Aortic Valve Replacement

Abstract: Introduction Transcatheter aortic valve replacement (TAVR) has been established as a standard of care for patients with severe aortic stenosis. We aim to study the predictors of acute kidney injury (AKI) after TAVR from a contemporary analysis using the National Inpatient Sample (NIS) database. Methods We performed a national analysis using the NIS database to evaluate predictors of acute kidney injury (AKI) after TAVR. Our study period was from 2015 to 2018, and we identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Among patients who developed AKI, 10,220 (9.5%) developed stage 1 AKI, 134 (0.1%) stage 2 AKI, and 1212 (1.1%) stage 3 AKI. A similar study by Abbas et al [51], utilizing the US National In-patient registry, reported a similar percentage at 11.5% (20,045/173,760). The 30-day mortality rate for AKI patients after TAVI is 7.8-29%.…”
Section: Acute Kidney Injurysupporting
confidence: 54%
“…Among patients who developed AKI, 10,220 (9.5%) developed stage 1 AKI, 134 (0.1%) stage 2 AKI, and 1212 (1.1%) stage 3 AKI. A similar study by Abbas et al [51], utilizing the US National In-patient registry, reported a similar percentage at 11.5% (20,045/173,760). The 30-day mortality rate for AKI patients after TAVI is 7.8-29%.…”
Section: Acute Kidney Injurysupporting
confidence: 54%
“…A recent study calls into question the causative role of CM in CI-AKI in patients undergoing TAVI. Because higher CM volumes did not result in an increase in CI-AKI incidence, the greatest risk comes from pre-procedural low GFR values and procedural factors such as periprocedural hypotension ( 165 , 166 ). The same can be said for MitraClip interventional procedures.…”
Section: Applicability In Non-coronary Interventional Proceduresmentioning
confidence: 99%
“…However, its role in predicting rehospitalization for cardiac disorders is less probable [22,23]. A meta-analysis made by Bianco et al [24] and a study conducted by Abbas et al [25] show a significantly higher rate of rehospitalizations for cardiac disorders in patients who underwent TAVI. Kodali et al [26] reported a similar rate of rehospitalizations for TAVI and SAVR (24.7% vs. 21.7%; P = 0.41).…”
Section: Discussionmentioning
confidence: 99%